Cardiff and Miller’s Road Trip (2004): Between Archive and Fiction - Buchanan, Alexandrina (Archivaria, 2012)
This paper uses an installation by the Canadian artists Cardiff and Miller to reflect on the nature of archival relationships and the possibilities of the archive as a fictional device. Road Trip is interpreted as a form of archive, creating relationships between different documentary layers that play out across time. It is suggested that the work’s impact derives from the tensions between the evidentiary and the narrative characteristics of the different “documents.” As an artwork, the constructed nature of Road Trip and its power to evoke an emotional response are obvious and intentional; nevertheless, these qualities are inherent in all archives. Art’s power to move reminds us of the need to be aware of the latent and potential layers of meaning within archives and the multifarious relationships they both embody and construct. RÉSUMÉ  Ce texte se fonde sur une installation des artistes canadiens Cardiff et Miller afin de réfléchir sur la nature des liens archivistiques, et sur les possibilités de l’archive comme appareil littéraire. L’auteure y interprète Road Trip comme une forme d’archives qui crée des liens entre les diverses couches documentaires qui se manifestent avec le temps. Elle suggère que l’impact de cette oeuvre provient des tensions entre les caractéristiques probantes et narratives des « documents » différents. Comme oeuvre d’art, la nature interprétée de Road Trip et son pouvoir de susciter une réaction émotive sont évidents et intentionnels; néanmoins, ces qualités sont inhérentes à toutes les archives. Le fait que l’art détient ce pouvoir de susciter une réaction émotive nous rappelle le besoin d’être conscient des diverses couches de sens cachées et potentielles à l’intérieur des archives, ainsi que des liens multiples qui sont incarnés par les archives, ou encore, construits par elles.